ГЕНЕТИЧЕСКИЙ ПОЛИМОРФИЗМ В РАЗВИТИИ ВНЕБОЛЬНИЧНОЙ ПНЕВМОНИИ У ДЕТЕЙ РАННЕГО ВОЗРАСТА - Сулейманова, Лола Исматуллаевна; Рахманкулова, Зухра Жандаровна; Камалов, Зайнутдин Сайфутдинович; Рузибакиева, Малика Руслановна (FORCIPE, 2022)